Multidimensional model of general contractile potential estimation of basic muscle groups in cadet judo athletes - Dopsaj, M.; Markovic, S.; Jovanovic, S. (XX Scientific Conference in physical education, sport and recreation - (Nis, Serbia, october 19-21st, 2017) - Book of Proceedings, 2017)
The aim of this paper is to define simple and initial mathematical model for estimation of general contractile potential of basic muscle groups in male cadet judo athletes for basic dimensions of isometric muscle force, both maximal isometric muscle force - SCORE_Fmax and maximal isometric explosive muscle force - SCORE_RFDmax. All tests were performed on 4 muscle groups as follows: sum for flexor muscles of both left and right hand (HG_SUM), back extensor muscles (DL), leg extensor muscles (LE) and ankle joint plantar flexors (PF). All tests were performed using isometric dynamometry method, with use of tensiometric probes. The sample in this research consisted of 12 male judo athletes aged 15.5.0.89 years, who compete in different weight categories within cadet age division. Statistical method applied was descriptive statistics, whereas models were calculated by application of mathematical modeling using multidimensional scaling. The defined models have explained 100% of measured variance (AdjR2 = 1.000), which implies absolute predictive potential for both contractility models considering characteristics of the sample. Standard error of prediction was 0.0022 points for SCORE_Fmax and 0.0028 points for SCORE_RFDmax.